Project Capabilities and Adults With Intellectual Disabilities: Towards Effective Interviewing for a Better Social Participation (LEARNing Landscapes, 2014)
This practice-based paper presents a series of tips and techniques for interviewing for a better social participation. While we worked on Project Capabilities, we learned valuable lessons we wished to share with practitioners and researchers who work within an inclusive perspective. We argue that qualitative interviewing requires skillful means that are not always an integral part of research preparation, and we share tips and techniques that we developed throughout the process. As we collected the qualitative data through one-on-one interviews, and taught participants to selffilm using iPads, we found that traditional interviewing techniques were too rigid to engage with people living with an intellectual disability. Instead, we used a blend of motivational interviewing and collaborative inquiry techniques, and built rapport with the participants through online social networking. Mobile technologies were also used to build rapport, empowering participants and allowing non-intrusive filming of interviews.
Keywords: practice-based; interview; social participation; inclusion; intellectual disability; qualitative; interview strategies; motivational interviewing; collaborative; inquiry; filming